Association Between Opioid Use and Risk of Sexual Dysfunction: A Systematic Review - Shahzadi, Mafia; Naseem, Tanzila; Unbrin, Aqila; Hussain, Aftab (Pakistan Journal of Humanities and Social Sciences, 2023)
Opioid use disorder (OUD) is defined by negative effects on oneself despite numerous efforts to stop it. Chronic opioid users have sexual dysfunctions such as erectile dysfunction, delayed ejaculation decreased libido, and sexual performance. To explore the association between the use of opioids and the risk of sexual dysfunction. This review was conducted from March 2023 to June 2023, and comprised of search on PsycINFO, MEDLINE, EMBASE, Google Scholar, OvidSP Science Direct, PubMed, Clinical Trials.gov, and Web of Science databases for experimental studies and randomized controlled trials related to OUDs published in peer-reviewed English-language journals between 2013 and 2023 (10 years). Of the 314 studies initially identified, 41(13%) were subjected to full-text assessment, and 10 were reviewed and analyzed (Figure). There were 2(20%) each study done in Egypt and Istanbul and 1(10) each in Germany, Canada, Spain, China, Poland, and Malaysia. All 10 (100%) studies were baes on opioid use and sexual dysfunction. Prospective studies showed that the occurrence of any sexual dysfunction ranged from 40% to 90% of opioid dependence. The most commonly studied observed sexual dysfunction is a lack of desire, erectile dysfunction, erectile dysfunction, and poor satisfaction. Our findings suggest that there is a significant link between opioid use and sexual dysfunction and that people who use opioids have higher rates of sexual dysfunction. Nevertheless, opioids have mind-altering properties that negatively affect various stages of the sexual cycle.